Assessment Of Dry Eye Status Using The Ocular Surface Disease Index (Osdi) In Cataract Surgery - Pandey, Rajneesh; Lal Rajoria, Madan; Sharan, Jayita; Tomar, Swati (Journal of Neonatal Surgery, 2025)
Background: Dry eye disease is multi-factorial and subsequently seen in patient who have undergone phacoemulsification and small incision cataract surgery. So this study was planned to assess the dry eye status among patients undergone phacoemulsification and small incision cataract surgery by using ocular surface disease index (OSDI). Materials & Methods: A prospective clinical study included 54 eyes of 54 patients of age 50-80 years suffering with cataract undergoing phacoemulsification or small incision cataract surgery. At the primary visit there were basic eye evaluation that included a detailed ocular and systemic history. Dry eye symptoms were evaluated using a validated Ocular Surface Disease Index (OSDI) questionnaire. The results were assessed before and 1 month after the surgery. Results: In 54 study patients, 66.7% women and 33.3% men, mean age was 74.08 ± 5.37. There was a significant increase in mean OSDI score after the cataract surgery: from 12.15 ± 10.34 to 13.79 ± 10.88, p =0.001. The postoperative increase in mean OSDI score was noted in both men (from 8.81 ± 7.65 to 10.5 ± 9.34, p = 0.054) and women group (from 13.59 ± 10.78 to 15.44 ± 11.35, p =0.008). Conclusions: this study concluded that the ocular surface was affected 1 month after the cataract surgery and the OSDI score increased. Further research is needed to evaluate if the changes observed in our study are long-term or not.